Comparison of denture base adaptation of rapid heat-cured resin acrylic using different cooling methods / Lee Wei May - Lee, Wei May (2019)
Introduction: 20 minutes rapid heat-cured resin acrylic is one of the denture base material improvisation to reduce processing time. Besides minimising polymerization shrinkage, cooling method plays an important role in producing denture base with good adaptation, leading to better treatment outcome. Aim: The purpose of this study is to investigate the effect of different cooling methods on denture base adaptation of rapid heat-cured resin acrylic. Materials and methods: Acron Express (Kemdent, UK) and Fast Heat Curing Acrylic (Huge Dent, China) are the resins used in this study. Both materials are 20 minutes heatcured acrylic. In the present study, denture base adaptation of Fast Heat Curing Acrylic was compared with ISO 20795-1:2013 certified Acron Express when both were cooled down following manufacturer’s instructions. On the other hand, comparison was done when Fast Heat Curing Acrylic was subjected to different cooling methods, namely the bench cooling and rapid cooling groups. Forty maxillary edentulous stone cast were duplicated from silicone mould (eight for each specimen groups). Putty index was used to produce denture base with standardized thickness. One master stone cast was scanned prior to fabrication process. Denture bases fabricated according to assigned groups were hydrated for 24 hours prior to scanning with 3Shape E1 laboratory scanner. The scanned Standard Tessellation Language (STL) file for each denture base was superimposed on the scanned STL file of maxillary edentulous stone cast using Materialise 3-matic software. Mean of root mean square (RMS) value and interquartile range (IQR) of overall numeric distance measurements were obtained to analyse accuracy and reproducibility of different specimen groups. Welch’s and two way analysis of variance were used to evaluate the differences between different material and cooling methods (α=0.5). iv Results: Fast Heat Curing Acrylic has lower RMS mean and narrower interquartile range than Acron Express when cooled down according to manufacturer’s instructions. No statistically significant difference in denture adaptation of Fast Heat Curing Acrylic when subject to different cooling methods. Conclusion: These results suggested Fast Heat Cure Acrylic is comparable to Acron Express when cool down according to manufacturer’s instructions. Although bench cooling is advocated when processing denture base with Fast Heat Curing Acrylic, rapid cooling is a viable alternative especially when shorter processing time is needed during community service